The Influence of Brand Image, Product Innovation, and Social Media Marketing Activities on Iphone Purchasing Decisions In Jakarta - Ponikasari Ponikasari; Mentiana Sibarani (Publikasi Indonesia, 2024)
This study aims to analyze the influence of brand image, product innovation and social media marketing activities on iPhone purchasing decisions in DKI Jakarta. This study is included in quantitative research. The population in this study were former iPhone users in DKI Jakarta who are currently or have used iPhone cellphones. The number of samples using the Cochran formula so that 100 respondents were obtained. The analysis method used is multiple linear regression. The results of the study show that brand image has a significant effect on iPhone purchasing decisions in DKI Jakarta, product innovation has a significant effect on iPhone purchasing decisions in DKI Jakarta, and social media marketing activities have a significant effect on iPhone purchasing decisions. Then, brand image, product innovation and social media marketing activities simultaneously (together) have a significant effect on iPhone purchasing decisions in DKI Jakarta. It is recommended that Apple can utilize platforms such as Instagram and TikTok to display user stories that illustrate how the iPhone supports their lifestyle. Local content that is tailored to trends in Jakarta, such as sustainability issues or urban productivity needs, can also increase appeal.